Specific properties of brown adipose tissue mitochondrial membrane - Houstĕk, J; Kopecký, J; Drahota, Z (Comparative biochemistry and physiology. B, Comparative biochemistry, 1978)
1. Mitochondrial membrane of brown adipose tissue compared to that of liver possesses a very high activity of oxidative enzymes but a low activity of ATPase. 2. The polypeptide composition of the mitochondrial membranes proves that the above differences in enzyme activities are due to increased content of oxidative enzymes and decreased content of ATPase in brown adipose tissue. 3. The inhibition of ATPase of brown adipose tissue mitochondria by aurovertin, oligomycin and DCCD indicates modified proportions between the components of the ATPase complex. 4. The organization of brown adipose tissue mitochondrial membrane in relation to its thermogenic function is discussed.
Keywords: křeček rodu Mesocricetus; Mesocricetus; Mitochondria; Cricetinae; Intracellular Membranes; intracelulární membrány; Adipose Tissue, Brown; zvířata; křečci praví; mitochondrie; hnědá tuková tkáň; Animals